Household Income Structure and Strategy Among Farmers In Subak Jatiluwih - I Putu Wisnumurti Utama Buda; Ketut Budi Susrusa; Anak Agung Ayu Wulandira Sawitri Djelant (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
The establishment of subak as A World Cultural Heritage significantly affected the income source among the farmer around the Subak Jatiluwih area. The farmer household income that had entirely relied on the agricultural sector, after the establishment, slowly shifted to the non-agricultural sector because of the higher income produced. This study aimed to know the social-economic characteristic, household income structure, and household income strategy among farmers in the Subak Jatiluwih area. This study conducted in Subak Jatiluwih, Penebel District, Tabanan Regency, and enrolled 40 farmers as the study participant. A quantitative and descriptive analysis employed to analyze the study data. The result showed that the social-economic characteristic of the farmer household in Subak Jatiluwih supported by working-age population with the mean age of 49, primary occupation as a farmer, accompanied by secondary occupation (37.5%), high educational background, and long duration of the farming experience (16-35%). The landowner status also significantly affected these characteristics. Most participants was a landowner and had 0.42 ha of farming land. The income strategy applied by the participants were intensification (70%), extensification (35%), dual-income (100%), and migration (40%). On-farm, off-farm, and non-farm sectors contributed to the household income structure, with non-farm sectors as the highest contributor (49.58%). We suggest the farmer household using an adequate income strategy. A system necessarily to design and implement to improve the farmer household skill in producing high-quality agricultural products.